PENEGAKAN HUKUM PELANGGARAN LALU LINTAS MELALUI SISTEM ELEKTRONIK: PERSFEKTIF HUKUM PENITENSIER - Nasution, M. Irsan (Ilmu Hukum, Sharia and Law Faculty, Sunan Gunung Djati Islamic State University of Bandung, 2023)
Law enforcement is an effort to bring justice, benefits, and legal clarity into the real world, including in the context of traffic violations. One of the innovations implemented in traffic law enforcement is the electronic ticketing system (E-Tilang), which has been officially adopted in almost every major city. E-Tilang aims to provide a solution to issues such as congestion and uncertainty in traditional ticketing processes by utilizing information technology. This system allows officers to send ticketing data online, provide ticket payment notification numbers, and enable violators to pay fines without having to appear in court. However, the implementation of E-Tilang is not without various challenges, including legal, technological, and public acceptance issues. From the perspective of correctional institutions, the application of E-Tilang also relates to the rehabilitation aspect for traffic violators, which can influence approaches to punishment and reintegration of offenders into society. This article will discuss in detail the mechanism of law enforcement for traffic violations through the electronic ticketing system, as well as the challenges and efforts faced in this context, including obstacles in law enforcement, the readiness of law enforcement officers, and factors affecting the effectiveness of this system. It is hoped that through this discussion, solutions can be found to improve the quality of traffic law enforcement that is more efficient and just.